2010
DOI: 10.1159/000295790
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Response to Apoptotic Cells Varies with the Apoptotic Trigger and Is Not Altered by a Deficiency in LRP Expression

Abstract: Rapid engulfment of apoptotic cells in the absence of inflammation is required for maintenance of normal tissue homeostasis. The low-density lipoprotein receptor-related protein-1 (LRP/CD91) is a receptor mediating interactions between macrophages and apoptotic cells, but recent reports have challenged the requirement of this surface protein in this process. To explore the role of LRP in the recognition of apoptotic cells, target cells were generated with two distinct inducers of apoptotic cell death, etoposid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
1
10
0
2
Order By: Relevance
“…1C). These results are consistent with published studies (12) and indicate that cells that die in response to different drugs can evoke distinct effects on inflammatory responses by engulfing macrophages.…”
Section: Actinomycin D-killed But Not Etoposide-killed Jurkat T Celsupporting
confidence: 93%
See 3 more Smart Citations
“…1C). These results are consistent with published studies (12) and indicate that cells that die in response to different drugs can evoke distinct effects on inflammatory responses by engulfing macrophages.…”
Section: Actinomycin D-killed But Not Etoposide-killed Jurkat T Celsupporting
confidence: 93%
“…Recent work has demonstrated that although phagocytosed equally well by macrophages, Jurkat T cells killed by etoposide are proinflammatory, whereas those killed by actinomycin D are immunosuppressive (12). However, the mechanisms by which actinomycin D-killed cells suppressed the immune response of the engulfing cells could not be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low-density lipoprotein receptor-related protein-1 (LRP/CD91) mediates macrophage-apoptotic cell interactions but its role was recently challenged. Kozmar et al [18] provide new data showing that the operative molecular pathway involved in apoptosis induction might affect the ensuing macrophage recognition of apoptotic cells and the resulting inflammatory response, thus indicating that monocyte recognition of apoptotic cells is more complex than previously thought.…”
mentioning
confidence: 99%